2018
DOI: 10.1002/stem.2912
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles Secreted by Nitric Oxide-Primed Mesenchymal Stromal Cells Boost the Engraftment Potential of Hematopoietic Stem Cells

Abstract: Patients with leukemia, lymphoma, severe aplastic anemia, etc. are frequently the targets of bone marrow transplantation, the success of which critically depends on efficient engraftment by transplanted hematopoietic cells (HSCs). Ex vivo manipulation of HSCs to improve their engraftment ability becomes necessary when the number or quality of donor HSCs is a limiting factor. Due to their hematopoiesis-supportive ability, bone marrow-derived mesenchymal stromal cells (MSCs) have been traditionally used as feede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Our group has shown in particular that MVs isolated from MSCs that have silenced AKT boost the engrafting capacity of HSCs interacting with them, while those isolated from stromal cells with a constitutively active AKT negatively affect the functionality of HSCs (Singh et al, 2016). In another study, we found that MVs isolated from MSCs treated with NO donors significantly improves the engraftment ability of HSCs (Jalnapurkar et al, 2018). MVs isolated from young and naive MSCs rejuvenate old HSCs and increase their engraftment ability via the transfer of MVs harboring autophagy‐related mRNAs (Kulkarni et al, 2019).…”
Section: Our Strategy For Expansion Of Hscs Using Evs Derived From Prmentioning
confidence: 94%
See 4 more Smart Citations
“…Our group has shown in particular that MVs isolated from MSCs that have silenced AKT boost the engrafting capacity of HSCs interacting with them, while those isolated from stromal cells with a constitutively active AKT negatively affect the functionality of HSCs (Singh et al, 2016). In another study, we found that MVs isolated from MSCs treated with NO donors significantly improves the engraftment ability of HSCs (Jalnapurkar et al, 2018). MVs isolated from young and naive MSCs rejuvenate old HSCs and increase their engraftment ability via the transfer of MVs harboring autophagy‐related mRNAs (Kulkarni et al, 2019).…”
Section: Our Strategy For Expansion Of Hscs Using Evs Derived From Prmentioning
confidence: 94%
“…Additionally, we have shown that NO increases the engrafting ability of juvenile HSCs, but has an adverse effect on adult HSC's engrafting ability (Jalnapurkar et al, 2016). Furthermore, we saw that MSCs primed with a donor of NO, SNP, significantly increased the engraftment potential of HSCs cocultured with them through the intercellular transfer of MVs containing mRNAs encoding HSC‐supporting genes (Jalnapurkar et al, 2018).…”
Section: Modulation Of Mscs For Therapeutic Purposementioning
confidence: 99%
See 3 more Smart Citations